Stress intensity factor of cracked steel tubular T and Y-joints under complex loads - Huang, Zhiwei. (2008)
In this study, fatigue performance of the tubular T&Y joints subjected to the combined loading was investigated. Based on the experimental and numerical investigation results, a set of parametric SIF equations was proposed by fracture mechanics method for design purpose.